Familial isolated hypoparathyroidism caused by a mutation in the gene for the transcription factor GCMB - Ding, Changlin (American Society for Clinical Investigation, 2001)
Hypoparathyroidism is characterized by hypocalcemia, hyperphosphatemia, and absent or markedly reduced circulating concentrations of parathyroid hormone. The transcription factor GCMB is predominantly, if not exclusively, expressed in parathyroid cells and is critical for development of the parathyroid glands in mice. Thus, in the present study we examined the GCMB gene, mapped to 6p23–24, as a candidate for isolated hypoparathyroidism. We defined the boundaries of the five exons of the human GCMB gene and then identified a large intragenic mutation in the GCMB genes of the proband of an extensive kindred with isolated hypoparathyroidism. Her parents and several other unaffected relatives were heterozygous for the mutation. Despite an absence of any history of consanguinity, microsatellite analysis showed shared genotypes that flanked the GCMB gene over a span of 5 cM, suggesting that both of the proband’s GCMB alleles had been derived from a single common ancestor. Analysis of additional, unrelated cases did not disclose the same mutation. We conclude that homozygous loss of function of the GCMB gene impairs normal parathyroid gland embryology and is responsible for isolated hypoparathyroidism in a subset of patients with this disease.